Exploring Self Identity: An Analysis of Audience Reception of Vlogs - Rizki Briandana; Feni Fasta; Eli Jamilah Mihardja; Amer Qasem (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
This study analyzed the interpretation of the self-identity projected by Tasya Farasha through her YouTube content. The development of youth identity today cannot be separated from the role of social media. In this context, Tasya Farasha’s content was examined from the viewpoint of the audience who watched it. This study uses a reception analysis methodology with focus group discussion as data collection technique. The informants in this study were selected based on criteria and classified based on three different universities in Jakarta. The result showed that the informants perceived the content of Tasya Farasya’s broadcast as a reference for youth in forming self-identity both culturally and persuasively in speech and action. The self-identity that Tasya Farasya projects led to a cosmopolitan identity. An identity that sees human’s equality in a community. This self-identity also shows its resistance to various dogmas that discriminate against differences.